Implementation of Financial Dashboards as Strategic Decision-Making Instruments in Public Service Agency (BLU) Institutions of the Ministry of Transportation - Sriyono; Abdul Hamid Arribathi; Nur Azizah (Journal of Renewable Energy and Smart Device, 2026)
This study aims to analyze the implementation of financial dashboards as strategic decision-making instruments in Public Service Agency (BLU) institutions within the Ministry of Transportation, especially on the Banten Maritime Polytechnic. The study employed a descriptive qualitative approach through a literature review by examining scientific journals, government regulations, official documents, BLU financial reports, and publications related to financial management information systems and dashboard implementation. The findings show that prior to the implementation of the financial dashboard, financial management processes, particularly Non-Tax State Revenue (PNBP) management, were still conducted conventionally through periodic and fragmented reports, resulting in delays in financial analysis and limitations in supporting strategic managerial decisions. Financial performance data show that PNBP realization increased from IDR 37.87 billion in 2021 to IDR 76.75 billion in 2022. Following the implementation of the financial dashboard in 2023, PNBP realization reached IDR 87.53 billion in 2023 and further increased to IDR 92.58 billion in 2025. The implementation of the dashboard integrated various financial modules into a single real-time digital platform capable of presenting financial information through interactive graphs, performance indicators, and analytical tables. Technically, the dashboard was developed using a centralized architecture that integrates data from e-Revenue, e-Planning, e-Expenditure, e-Revision, e-Honorarium, e-Official Travel, and e-PKP modules into a unified database that supports real-time data synchronization and financial analytics. The dashboard system enabled institutional leaders to monitor revenue realization, evaluate financial performance, identify revenue trends, compare inter-period financial achievements, and formulate data-driven financial policies more efficiently. The financial dashboards improve transparency, accountability, effectiveness, and responsiveness in BLU financial governance while strengthening strategic decision-making processes within public sector institutions.